A ligand-inducible epidermal growth factor receptor/anaplastic lymphoma kinase chimera promotes mitogenesis and transforming properties in 3T3 cells - Piccinini, Gina; Bacchiocchi, Roberta; Serresi, Michela; Vivani, Caterina; Rossetti, Silvia; Gennaretti, Claudia; Carbonari, Damiano; Fazioli, Francesca (The Journal of biological chemistry, 2002)
Oncogenic rearrangements of the anaplastic lymphoma kinase (ALK) gene, encoding a receptor type tyrosine kinase, are frequently associated with anaplastic large cell lymphomas. Such rearrangements juxtapose the intracellular domain of ALK to 5'-end sequences belonging to different genes and create transforming fusion proteins. To understand how the oncogenic versions of ALK contribute to lymphomagenesis, it is important to analyze the biological effects and the biochemical properties of this receptor under controlled conditions of activation. To this aim, we constructed chimeric receptor molecules in which the extracellular domain of the ALK kinase is replaced by the extracellular, ligand-binding domain of the epidermal growth factor receptor (EGFR). Upon transfection in NIH 3T3 fibroblasts, the EGFR/ALK chimera was correctly synthesized and transported to the cell surface, where it was fully functional in forming high versus low affinity EGF-binding sites and transducing an EGF-dependent signal intracellularly. Overexpression of the EGFR/ALK chimera in NIH 3T3 was sufficient to induce the malignant phenotype; the appearance of the transformed phenotype was, however, conditionally dependent on the administration of EGF. Moreover, the EGFR/ALK chimera was significantly more active in inducing transformation and DNA synthesis than the wild type EGFR when either was expressed at similar levels in NIH 3T3 cells. Comparative analysis of the biochemical pathways implicated in the transduction of mitogenic signals did not show any increased ability of the EGFR/ALK to phosphorylate PLC-gamma and MAPK compared with the EGFR. On the contrary, EGFR/ALK showed to have a consistently greater effect on phosphatidylinositol 3-kinase activity compared with the EGFR, indicating that this enzyme plays a major role in mediating the mitogenic effects of ALK in NIH 3T3 cells.